2013
DOI: 10.1111/j.1600-0706.2013.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure of ant–plant mutualistic networks

Abstract: The structure of mutualistic networks provides insights into ecological and coevolutionary dynamics of interacting species. However, the spatial effect has only recently been incorporated as a factor structuring mutualistic networks. In this study, we evaluated how the topological structure and species turnover of ant–plant mutualistic networks vary over a spatial gradient. We showed that although the ant and plant composition of networks changed over space, the central core of generalist species and the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
146
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(159 citation statements)
references
References 47 publications
4
146
1
8
Order By: Relevance
“…That close and distant networks were more and less similar than expected, respectively, implies that some kind of assortment of species and interactions is taking place in relation to distance. Although on a spatial scale two orders of magnitude smaller, other studies have found a similar decrease in similarity for species in ant-plant mutualistic networks [11] and for plant species and interactions in plant -pollinator networks [13]. Burkle & Alarcó n [10], however, found no correlation between geographical distance and the similarity in plants, pollinators or interactions along a 3 km gradient.…”
Section: Discussion (A) Community Similaritymentioning
confidence: 85%
See 2 more Smart Citations
“…That close and distant networks were more and less similar than expected, respectively, implies that some kind of assortment of species and interactions is taking place in relation to distance. Although on a spatial scale two orders of magnitude smaller, other studies have found a similar decrease in similarity for species in ant-plant mutualistic networks [11] and for plant species and interactions in plant -pollinator networks [13]. Burkle & Alarcó n [10], however, found no correlation between geographical distance and the similarity in plants, pollinators or interactions along a 3 km gradient.…”
Section: Discussion (A) Community Similaritymentioning
confidence: 85%
“…nestedness, modularity and connectance) has usually been identified as stable [11,15,16,18,23]. None of these studies have quantified the fidelity of partner compositions, and here we suggest that it may be seen as a deeper fine-scaled layer contributing to our understanding of the dynamics of global network structures.…”
Section: (C) Partner Fidelitymentioning
confidence: 94%
See 1 more Smart Citation
“…In order not to overestimate the plant species with more number of flowers, we considered as interaction frequency only the interactions among individuals within transects. To test whether the composition of plants and wasps shifts along the core-periphery gradient of the networks in each area, we defined the core of generalist species according to Dáttilo et al (2013b). The species that exhibit a Cp > 1 are species with a higher proportion of interactions in relation to other species of the same group and are therefore considered core species of the network.…”
Section: Resultsmentioning
confidence: 99%
“…GUIMARÃES; IZZO, 2013;DÁTILLO;DEL-CLARO, 2013), coloca as plantas sobre uma enorme pressão evolutiva causada principalmente por herbívoros (MARQUIS; RICKLEFS; ABDALA-ROBERTS, 2012;THOMPSON, 2013), sendo a herbivoria considerada a interação antagonista de maior importância (STRAUSS; CONNER; RUSH, 1996, STRAUSS, 1997PRICE et al, 2011), já que pode comprometer diretamente o crescimento, a reprodução e a sobrevivência das plantas (TOREZAN-SILINGARDI, 2011). As plantas, por sua vez, desenvolveram estratégias de defesas químicas e físicas a fim de reduzir os danos e ataques causados por insetos (MARQUIS, 2012;.…”
Section: Introductionunclassified